Analisis Pengaruh Pembangunan Infrastruktur Terhadap Pertumbuhan Ekonomi di Kabupaten Langkat - Rafilladuri; Anggia Ramadhan; Rahmat Sembiring (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study investigates the impact of infrastructure development on economic growth in Langkat Regency, North Sumatra, Indonesia. The research focuses on four main variables: road availability, healthcare services, educational infrastructure, and investment allocation. Despite its rich natural resources and economic potential, Langkat Regency faces challenges in achieving sustainable economic growth due to inadequate and uneven infrastructure distribution. Employing a quantitative research approach, this study uses time-series secondary data from 2015 to 2024 sourced from the Central Bureau of Statistics of Langkat Regency. Multiple linear regression analysis is applied to examine the partial and simultaneous effects of infrastructure components on regional economic performance. The findings are anticipated to show that infrastructure development has a significant and positive influence on economic growth, particularly by improving access, reducing logistical costs, increasing productivity, and attracting investment. The results of this research are expected to provide empirical evidence and policy recommendations for local governments in formulating strategic infrastructure planning aimed at fostering inclusive and sustainable economic development